The link between cultural due diligence and socio-cultural post-merger integration management as a critical success factor in M&As - Christoph Dörrenbächer; Natalie Witzmann (Hochschule für Wirtschaft und Recht Berlin, IMB Institute of Management Berlin, 2015)
With the unchanging high failure rate of M&As, recent research is putting an increasing emphasis on Cultural Due Diligence (CDD) and socio-cultural Post-Merger Integration (PMI) Management. Nevertheless, the state of the art on CDD is still rare, leading to the fact that its actual value for a successful PMI remains unclear. Addressing this gap is the basic objective of this paper. In more detail the paper tries to clarify whether CDD is a necessary prerequisite for a successful PMI. The paper finds that the CDD process creates considerable value for the subsequent PMI as it facilitates a fast and smooth cultural integration and as such accelerates the operative integration of M&As. – – Die andauernd hohe Misserfolgsrate bei M&A hat zu einer intensiven wissenschaftlichen Beschäftigung mit Cultural Due Diligence (CDD) und sozio-kulturellem Post-Merger Integrationsmanagement geführt. Unklar ist jedoch inwieweit CDD zu einer gelungenen Post-merger Integration beiträgt. Am Beispiel einer Fallstudie zeigt der hier vorliegende Aufsatz, dass CDD eine wichtig Voraussetzung für eine gelungene Post-merger Integration ist, da er eine schnelle und reibungsarme kulturelle Integration ermöglicht und damit auch die operative Integration beschleunigt.
Keywords: 650; Due Diligence; Übernahme; Post-Merger-Integration; Unternehmenskultur; Erfolgsfaktor